2018
DOI: 10.1007/978-3-319-72170-5_30
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Contribution of Gestures to Mathematical Argumentation Processes from a Semiotic Perspective

Abstract: A multimodal perspective on mathematics thinking processes is addressed through the semiotic bundle lens and considering a wide notion of sign drawing from Vygotsky's works. Within this frame, the paper focuses on the role of gestures in their interaction with the other signs (speech, in particular) and investigates the support they can provide to mathematical argumentation processes. A case study in primary school in the context of strategic interaction games provides data to show that gestures can support st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…In the teaching of mathematics, teachers routinely and regularly produce gestures along with their speech which, I argue have the potential to influence pupils' learning. Research has shown that the combination of teachers' speech and gesture often provides greater insight into learners' mathematical knowledge and understanding than either words or gestures alone (McNeill, 1992;Sabena, 2018). This access to knowledge and understanding that gestures may enable, is necessary in multilingual classes, where the LOLT is neither the teacher's nor the learners' first.…”
Section: Contribution To the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In the teaching of mathematics, teachers routinely and regularly produce gestures along with their speech which, I argue have the potential to influence pupils' learning. Research has shown that the combination of teachers' speech and gesture often provides greater insight into learners' mathematical knowledge and understanding than either words or gestures alone (McNeill, 1992;Sabena, 2018). This access to knowledge and understanding that gestures may enable, is necessary in multilingual classes, where the LOLT is neither the teacher's nor the learners' first.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…McNeill (1992) posited that, "gestures are an integral part of language as much as are words, phrases and sentences" (p. 2). My focus on teachers' gestures is informed by the large body of research showing that gestures contribute to communication in a wide range of settings (Kendon, 2004;Sabena, 2018). The use of visualization processes such as gestures in teaching mathematics is an important component to help learners to build their own adequate internal representations of mathematical ideas.…”
Section: Gestures and Multilingual Mathematics Classroom Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…A partire poi da ricerche riguardanti il cervello e il funzionamento neuronale (Gallese & Lakoff, 2005) e gli aspetti semiotici della comunicazione (Kress, 2000) si è affermato in didattica della matematica il concetto di "multimodalità" inteso come «[...] la coesistenza e l'importanza di diverse modalità o risorse nei processi di apprendimento-insegnamento [...]» come parole, gesti, simboli, posizioni del corpo, toni della voce (Sabena et al, 2019, p. 19). In particolare, numerosi studi si sono soffermati sul ruolo dei gesti, mostrando il ruolo preminente di questi ultimi e dell'esperienza senso-motoria nella costruzione e condivisione di significati, nel dispiegarsi dell'argomentazione e della discussione matematica e nello sviluppo di nuove conoscenze (Arzarello et al, 2009;Arzarello et al, 2005;Radford, 2014;Sabena, 2018). Un altro filone di ricerca si è invece concentrato sul ruolo del corpo nella sua interezza e del movimento nell'emergere dei concetti matematici e nel favorire la loro comprensione: ne sono un esempio gli studi di Susan Gerofsky (2011Gerofsky ( , 2016Gerofsky ( , 2018, che, con il progetto Graph & Gestures, ha messo in luce la maggiore capacità intuitiva degli studenti che utilizzano movimenti a largo spettro, coinvolgendo…”
Section: Ddmunclassified
“…In the more radical approaches, mathematics is not considered a body of transcendental ideas, but as part of concrete human activity, dependent on bodily and sensuous experience. As a consequence of the increased focus on embodiment, the role of gestures in and for thinking has also gained attention in educational research and has been found important in the formation of mathematical concepts, for example, in teaching-learning about spatial concepts (Elia & Evangelou, 2014), numerical relations (Sabena, 2018), and algebraic structures (Radford, 2009). Despite the increasing focus on the role of the body in mathematics thinking and learning, and the acceptance that young children use artefacts and gestures while solving mathematical tasks, the literature is still sparse on the more precise role of the body in young children's mathematical thinking.…”
Section: Introductionmentioning
confidence: 99%